2018
DOI: 10.1074/jbc.ra118.002894
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of the kinase gene SGK1 by progesterone activates the AP-1–NDRG1 axis in both PR-positive and -negative breast cancer cells

Abstract: Preoperative progesterone intervention has been shown to confer a survival benefit to breast cancer patients independently of their progesterone receptor (PR) status. This observation raises the question how progesterone affects the outcome of PR-negative cancer. Here, using microarray and RNA-Seq–based gene expression profiling and ChIP-Seq analyses of breast cancer cells, we observed that the serum- and glucocorticoid-regulated kinase gene (SGK1) and the tumor metastasis–suppressor gene N-Myc downstream regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…The HIF-regulated N-myc downstream regulated gene (NDRG1) is predominantly overexpressed in perinecrotic areas and ER-negative breast cancer and is predictive for bevacizumab response and prognostic for survival (80,81). Homozygous loss-of-function NDRG1 in humans causes a neurological disorder with nerve demyelination and NDRG1 manipulation in breast cancer cell lines deregulated lipid droplet storage, although its exact metabolic function and discrepancies in its reported effects on migration and breast cancer progression require further clarification (81,82).…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…The HIF-regulated N-myc downstream regulated gene (NDRG1) is predominantly overexpressed in perinecrotic areas and ER-negative breast cancer and is predictive for bevacizumab response and prognostic for survival (80,81). Homozygous loss-of-function NDRG1 in humans causes a neurological disorder with nerve demyelination and NDRG1 manipulation in breast cancer cell lines deregulated lipid droplet storage, although its exact metabolic function and discrepancies in its reported effects on migration and breast cancer progression require further clarification (81,82).…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Posttranscriptional regulation, including RNA processing, RNA degradation and translation is an essential aspect of the regulation of gene expression. Previous studies demonstrated that the disorder of posttranscriptional regulation is associated with the occurrence and development of various cancers [21][22][23]. Many RBPs bind to sequence-speci c motifs or RNA secondary structures through unique modular arrangements of individual RNA-binding domains to play the roles in the homeostatic regulation of gene expression [24,25], which in uence the progression of many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Increased NDRG1 expression reduced the activation of multiple cellular kinases and cell migration. 21 These inconsistent views may be due to the different models used, suggesting that SGK1 performs specific functions in different situations.…”
Section: Functions and Mechanisms Of Sgk1 In Oncologymentioning
confidence: 99%
“… 1 , 3 , 14 , 15 SGK1 has been previously reported in hypertension, diabetes, hypercoagulability, and autoimmune disease. 5 , 16 , 17 A growing number of recent studies reveal a role for SGK1 in human tumors such as glioblastoma, 18 20 breast, 21 25 colorectal, 26 28 prostate, 29 31 thyroid, 32 ovarian, 33 myeloma, 11 and non-small cell lung cancer 34 ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%